Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
ISSN 0805-505X ISBN 82-8062-172-5
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização